THE ROLE OF THE GOVERNMENT IN INCREASING POLITICAL PARTICIPATION OF PERSONS WITH DISABILITIES - Melyana R Pugu; Hotmaria Hertawaty Sijabat; Abdul Rozak (RADJA PUBLIKA, 2025)
People with disabilities often face various barriers to participating in the political process, both in the context of elections and in legislative activities. The role of the government is a key factor in overcoming these barriers through inclusive policies that ensure accessibility, equality, and non-discrimination for people with disabilities. The government can provide disability-friendly election facilities, special aids, and assistance to guarantee their right to vote. In addition, cooperation with disability advocacy organisations and public education are important strategies for changing stigma and supporting the creation of an inclusive political environment. With these measures, the political participation of persons with disabilities can be increased, enabling them to play an active role as voters and political decision-makers.